Perbedaan Kekuatan Otot Genggam Tangan Antara Atlet Calisthenics Dengan Pekerja Konstruksi Bangunan - Wibowo, Gatra Hadimuti; Fiana, Dewi Nur; Fauzi, Ahmad; Berawi, Khairunnisa (CV. Jasa Sukses Abadi, 2024)
Physical activity has an important role in increasing muscle strength. High intensity physical activity can build muscle mass ,endurance and increase muscle strength compared to low intensity physical activity. One way to determine the strength of the hand or upper extremity muscles can be measured by the strength of the hand grip muscles. In this study, researchers wanted to look at the differences in hand grip muscle strength between calisthenics athletes and building construction workers. The research was conducted with a cross sectional approach using total sampling techniques. Data was taken in November 2023 at Saburai Field and Unila Bandar Lampung with 40 calisthenics athletes and 40 building construction workers who met the inclusion and exclusion criteria. Data was obtained by measuring using a Camry dynamometer. Data were analyzed using the Independent T-test. The result showed that there was a significant difference between the hand grip muscle strength of calisthenics athletes and building construction workers with a p value of 0.000. It concluded that there was a significant difference between the hand grip muscle strength of calisthenics athletes and building construction workers.